Media Pembelajaran Flipchart di TK Muyang Mersa Kabupaten Takengon - Suminah Suminah (Neolectura, 2022)
This research is motivated by the lack of learning motivation of children at Muyang Mersa Kindergarten, Linge District, Central Aceh Regency. The lack of value for children's learning motivation is evidenced by the results of children's learning which shows 18.78 with categories that still need guidance. This study aims to determine how the application of flipchart learning media in Muyang Mersa Kindergarten, Linge District, Central Aceh Regency. The method used in this research is classroom action research (CAR) with Kurt Lewin's model. Comparison of activity results after using Flipchart media the average value of pre-cycle children reached 18.78, in cycle I reached 21.64 and cycle II was 23.87, the percentage of children's learning completeness using Flipchart media in cycle I reached 40% and cycle II 59% occurred. 19% increase after using Flipchart media a significant improvement. Conclusion Flipchart media in increasing children's learning motivation increased by a total score of 41.7% with a very well developed category (BSB) Then in the second cycle it increased again with a total score of 58.3% with a very well developed category (BSB). The teacher provides picture media in the form of a calendar-sized flipchart, chooses the appropriate color to make it look attractive to the child, the teacher places the flipchart learning media in the right position so that it is clearly visible to the child after that the teacher also uses simple language.